Arsenic exposure alters lung function and airway inflammation in children: A cohort study in rural Bangladesh. (April 2017) - Ahmed, Sultan; Akhtar, Evana; Roy, Adity; von Ehrenstein, Ondine S.; Vahter, Marie; Wagatsuma, Yukiko; Raqib, Rubhana
Abstract: Exposure to arsenic has been associated with increased risk of reduced lung function in adults, but the adverse impacts in early life are unclear. We aim to examine whether prenatal and childhood arsenic exposure is associated with reduced lung function and increased airway inflammation in school-aged children. Children born in the MINIMat cohort in rural Bangladesh were evaluated at 9 years of age ( n = 540). Arsenic exposure was assessed in urine (U-As) that was collected from mothers during early pregnancy and their children aged 4.5 and 9 years. In the 9-year-old children, lung function was assessed using spirometry and airway inflammation was assessed by the NIOX MINO system. C-reactive protein (CRP) and Clara cell secretory protein (CC16) concentrations were measured in plasma by immunoassays. The U-As concentrations in 9-year-old children were lower (median 53 μg/l) compared to their mothers (median 76 μg/l). Maternal U-As (log2 transformed) was inversely associated with forced vital capacity (FVC) and forced expiratory volume at 1 s (FEV1) (β = − 12; 95% CI: − 22, − 1.5; p = 0.031 and β = − 12; 95% CI: − 22, − 1.9; p = 0.023, respectively) in all children, and the associations were stronger in boys and among children with adequate height and weight, as well as among those whose mothers had higher percentages of methylarsonic acid (MMA) and lower percentages of dimethylarsinic acid (DMA). U-As (log2 transformed) at 4.5 and 9 years was positively associated with fractional exhaled nitric oxide (FENO ) concentrations in boys (β = 0.89; 95% CI: 0.13, 1.66; p = 0.022 and β = 0.88; 95% CI: 0.16, 1.61; p = 0.017, respectively) but not in girls. Increased CC16 concentrations were associated with higher lung function indices. In conclusion, our findings suggest that prenatal arsenic exposure is related to impaired lung function, while childhood exposure may increase airway inflammation, particularly in boys. Highlights: Prenatal arsenic exposure tends to reduce lung function in older children. Childhood arsenic exposure is associated with increased airway inflammation. Stronger associations are noted in boys compared to girls.